Yak Gut Microbiota: A Systematic Review and Meta-Analysis - Su, Yuxin; Su, Junhong; Li, Fanglin; Tian, Xiaojing; Liu, Zewen; Ding, Gongtao; Bai, Jialin; Li, Zhuo; Ma, Zhongren; Peppelenbosch, Maikel P. (Frontiers in Veterinary Science, 2022)
The yak (Bos grunniens) is closely related to common cows (Bos taurus), but is clearly a distinct species. Yaks are of substantial importance to food and leather production in certain high altitude regions of Asia. The animal is increasingly elsewhere as well, mainly because of the perceived health benefits of its milk. Like all ruminants, the animal harbors a complex community of microbial cells in its gut, crucial for its physiology. Despite yaks being important domestic animals, the composition of its gut microbiota and how composition is guided by its specific high altitude environment remains largely uncategorized. Hence, online databases (Embase, Medline ALL, Web of Science Core Collection, Cochrane Central Register of Controlled Trials and Google Scholar) were searched for articles on yak intestinal microbiota. Pooled taxonomic abundance was compared between regions, sexes, different age groups and feeding patterns. The gut microbiota distribution across different yak intestinal segments was established through pooled average taxonomic abundance. A total of 34 studies were met inclusion criteria and yielded information on 982 unique yak gut microbiota samples. Analysis of overall pooled microbiota revealed a segmented microbial community composition of the yak gut. Yak rumen microbiota was significantly influenced by difference in region, sex and feeding patterns, the latter factor being dominant in this respect. Yak microbiome is shaped by feeding strategy and provides an obvious avenue for improving health and productivity of the animal. More generally, the current segmental description of physiological gut microbiome provides insight into how the microbiology of this animal has adapted itself to help comping yaks with its high altitude habitat.